TECHNO-PEDAGOGY: WHAT IS THE ROLE OF PROSPECTIVE TEACHERS IN PREPARING FOR LEARNING IN THE DIGITAL ERA? - Setiasih, Ocih (Prodi Teknologi Pendidikan, 2021)
Digital media is very closely related to life, making its role very important in building life's culture. The role of digital media also affects the style or method of carrying out learning. Therefore, there needs to be an exploratory study in looking at learning using digital media. The purpose of the research is to decrypt the role of digital media in influencing prospective educators' learning styles (students) and explore prospective educators (students) to face learning in the digital age. This research method phenomenology. The subject of study is educational students or prospective educators. Data collection is conducted by open survey and questionnaire methods. Quantitative data were analyzed using descriptive statistics, and qualitative data analysis was performed by reducing data, looking for relationships between themes and levers. The results showed that the digital media's role is vast in building the learning style of prospective teachers. The role is shown with ease of access obtained by prospective teachers and many resources that reference knowledge development. Besides, it turns out that prospective educators can analyze/vaccinate the learning process using digital media. This shows that prospective teachers are ready to face the challenges of learning in the digital age and can make a breakthrough in learning in the digital age